Perception of Greek vowels by children with and without ADD/H - Οκαλίδου Αρετή; Βούλτσιος Ηλίας; Fourakis, Marios; Γουδήρας Δημήτριος (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF